1966
DOI: 10.1055/s-0038-1655648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenobarbital and Glutethimide on Biological Half-Life of Warfarin

Abstract: SummaryThe administration of phenobarbital or glutethimide significantly decreased the half-life of warfarin in 21 of 34 hospitalized patients. Patients who demonstrated a decrease could not be distinguished from apparent non-responders by age, weight, sex, or race. These sedatives did not detectably affect gastrointestinal absorption of warfarin. The observed decrease in warfarin half-life supports the concept that barbiturates and other drugs can increase the concentration of some drug-metabolizing enzymes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Amobarbital 112 , phenobarbital 107 , secobarbital 107 has also been reported to diminish pharmacological activity of warfarin. A number of other hypnosedatives and anticonvulsant drugs such as gluthethimide 107,113,114 , carbamazepine 115,116,117,118 and phenytoin 119 induce metabolism of warfarin. Benzodiazepines do not interact significantly with warfarin 1 .…”
Section: Drugs Causing Enzyme Inductionmentioning
confidence: 99%
“…Amobarbital 112 , phenobarbital 107 , secobarbital 107 has also been reported to diminish pharmacological activity of warfarin. A number of other hypnosedatives and anticonvulsant drugs such as gluthethimide 107,113,114 , carbamazepine 115,116,117,118 and phenytoin 119 induce metabolism of warfarin. Benzodiazepines do not interact significantly with warfarin 1 .…”
Section: Drugs Causing Enzyme Inductionmentioning
confidence: 99%
“…It is probably that all barbiturates can induce the metabolism of all the coumarin anticoagulants. Time for significant induction varies but can be as short as 1 or 2 days (Corn, 1966). After withdrawal of the barbiturate, some weeks are often required for return of normal metabolic rates (MacDonald and Robinson, 1968).…”
Section: Metabolismmentioning
confidence: 99%
“…In normal subjects, Udall (1975) found significant alteration in anticoagulant activity after adding phenobarbitone in 9 out of 10 cases. Corn (1966) showed that the warfarin half-life falls in 13 out of 21 patients after treatment with phenobarbitone.…”
Section: Induction Of Drug Biotransformationmentioning
confidence: 99%
“…Besides barbiturates, glutethimide shortens the half-life of warfarin (Corn, 1966) and also alters the anticoagulant activity to a clinically significant extent (Udall, 1975),…”
Section: Induction Of Drug Biotransformationmentioning
confidence: 99%